PENINGKATKAN BERPIKIR KRITIS DAN HASIL BELAJAR IPA MELALUI MODEL PROBLEM BASED LEARNING - Kristiawan, Renaldo; Purbosari, Para Mitta; Sularmi, Sularmi (Universitas Veteran Bangun Nusantara, 2021)
Abstract The purpose of the study was to improve students' critical thinking skills and science learning outcomes through a problem based learning model for class V SD Negeri Begajah 01 for the 2020/2021 academic year. This research is a classroom action research conducted at SD Negeri Begajah 01 for the 2020/2021 academic year. The subjects of this research are students and teachers of class V, the object of this research is critical thinking skills and student learning outcomes through problem based learning models. Data collection techniques using test and non-test methods. The instruments used in conducting research evaluations are: questionnaires, observations, interviews, and tests. The research sample consisted of 22 students consisting of 9 males and 13 females with 2 research cycles. The analysis technique uses quantitative data analysis, comprehensive descriptive data and qualitative data analysis. The results of the research cycle I showed that students who achieved critical mastery in the first cycle were 72.72% (minimum critical enough) in the second cycle increased to 100% (minimum critical enough) and the learning outcomes in the first cycle were 72.72% and the second cycle was 84, 39%. Thus, from this study, it can be concluded that problem-based learning can improve critical thinking skills and learning outcomes for class V SDN Begajah 01 for the academic year 2020/2021.